Growth and hormone profiling in children with congenital melanocytic naevi. (1st December 2015) - Waelchli, R.; Williams, J.; Cole, T.; Dattani, M.; Hindmarsh, P.; Kennedy, H.; Martinez, A.; Khan, S.; Semple, R.K.; White, A.; Sebire, N.; Healy, E.; et al.
Summary: Background: Multiple congenital melanocytic naevi (CMN) is a rare mosaic RASopathy, caused by postzygotic activating mutations in NRAS . Growth and hormonal disturbances are described in germline RASopathies, but growth and hormone status have not previously been investigated in individuals with CMN. Objectives: To explore premature thelarche, undescended testes, and a clinically abnormal fat distribution with CMN through prospective endocrinological assessment of a cohort of subjects with CMN, and a retrospective review of longitudinal growth of a larger group of patients with CMN from outpatient clinics (which included all subjects in the endocrinological assessment group). Patients and methods: Longitudinal growth in a cohort of 202 patients with single or multiple CMN was compared with the U.K. National Child Measurement Programme 2010. Forty‐seven children had hormonal profiling including measurement of circulating luteinizing hormone, follicle‐stimulating hormone, thyroid stimulating hormone, adrenocorticotrophic hormone, growth hormone, prolactin, pro‐opiomelanocortin, estradiol, testosterone, cortisol, thyroxine, insulin‐like growth factor‐1 and leptin; 10 had oral glucose tolerance testing 25 had dual‐energy X‐ray absorptiometry scans for body composition. Results: Body mass index increased markedly with age (coefficient 0·119, SE 0·016 standard deviation scores per year), at twice the rate of the U.K. population, due to increased adiposity. Three per cent of girls had premature thelarche variant and 6% of boys had persistent undescended testes. Both fat and muscle mass were reduced in areas underlying large naevi, resulting in limb asymmetry and abnormal truncal fat distribution. Anterior pituitary hormone profiling revealed subtle and variable abnormalities. Oral glucose tolerance tests revealed moderate–severe insulin insensitivity in five of 10, and impaired glucose tolerance in one. Conclusions: Interpersonal variation may reflect the mosaic nature of this disease and patients should be considered individually. Postnatal weight gain is potentially related to the underlying genetic defect; however, environmental reasons cannot be excluded. Naevus‐related reduction of fat and muscle mass suggests local hormonal or metabolic effects on development or growth of adjacent tissues, or mosaic involvement of these tissues at the genetic level. Premature thelarche and undescended testes should be looked for, and investigated, as for any child.